Construction of The Integration Model of Social Emotional Learning Based on Islamic Education in The Independent Curriculum of Elementary School Gugus Panglima Sulung Tembilahan - Nurlaila Nurlaila; Zamsiswaya Zamsiswaya; Asmal May (Dinasti International Journal of Education Management And Social Science, 2025)
This study is to answer the formulation of the problem of how to develop an integration model of social emotional learning based on Islamic education in the Independent Curriculum of Elementary School Gugus Panglima Sulung Tembilahan and how effective the integration model of social emotional learning based on Islamic education in the Independent Curriculum. This R & D research was conducted using a mixed methods approach. Data collection techniques in this study used interviews, documentation, and tests. Data analysis techniques with the ADDIE model (analyze, design, develop, implementation and evaluation). The results of this development research are the PSE integration model based on Islamic Education in the form of the SEMBADA, SELAMAT, SETIA, SELADA, and SELASIH models. This model has been proven to be able to improve social emotional competence based on Islamic education in students as evidenced quantitatively and qualitatively by analyzing the pretest results (before being given intervention) and posttest (after being given intervention). This model is considered feasible and relevant to be applied in the Independent Curriculum.